Size-dependent magnetic properties of nanocrystalline yttrium iron garnet powders - Rajendran, M.; Deka, Sasanka; Joy, Pattayil Alias; Bhattacharya, Asish K. (Journal of Magnetism and Magnetic Materials, 2006)
Yttrium iron garnet (YIG) powders with particle sizes of 9, 14, 25 and 60 nm have been synthesised and their magnetic properties have been studied as a function of particle size and temperature. The particles with sizes of 9 and 14 nm exhibited superparamagnetism. The blocking temperature (T-B) decreased with decreasing particle size, whereas the anisotropy constant (K) increased. The saturation magnetisation (M-s) decreased with decreasing particle size. These variations are attributed to large surface-to-volume ratios in nanoparticles where the surface moments are predominant. (c) 2005 Published by Elsevier B.V.
Keywords: anisotropy constant; Magnetism; Nanoparticles; Superparamagnetism; YIG

Semi-synthesis of deoxyartemisinin - Bhattacharya, Asish K.; Pathak, Ashish K.; Sharma, Ram P. (Mendeleev Communications, 2007)
The reaction of artemisinin with aluminium-nickel chloride hexahydrate in THF or nickel boride in MeOH furnishes deoxyartemisinin in an excellent yield.

SbCl(3) as a highly efficient catalyst for the acetylation of alcohols, phenols, and amines under solvent-free conditions - Bhattacharya, Asish K.; Diallo, Mamadou A.; Ganesh, Krishna N. (Synthetic Communications, 2008)
Antimony trichloride has been found to be an efficient and expedient catalyst for the acylation of alcohols, phenols, amines, and sugars with acetic anhydride in high yields and in a short reaction time under solvent-free conditions at room temperature. Also, racemization of chiral alcohols and epimerization of sugars were not observed in any of the substrates.
Keywords: acetic anhydride; acetylation; antimony trichloride; solvent-free conditions

Synthesis and in vitro study of 14-aryl-14H-dibenzo[a.j]xanthenes as cytotoxic agents - Bhattacharya, Asish K.; Rana, Kalpeshkumar C.; Mujahid, Mohammad; Sehar, Irum; Saxena, Ajit K. (Bioorganic & Medicinal Chemistry Letters, 2009)
A simple and expedient method for the synthesis of a series of 14-aryl-14H-dibenzo[a.j]xanthenes is described through a one-pot condensation of beta-naphthol with aryl aldehydes catalysed by TaCl(5) under solvent-free conventional heating. The major advantages of the present method are: high yields, less reaction time, solvent-free condition and easy purification of the products. The synthesized 14-aryl-14H-dibenzo[a.j]xanthenes were evaluated against a panel of six human cancer lines of different tissues. Synthesized compound 30 showed IC(50) of 37.9 and 41.3 mu M against Colo-205 and 502713, respectively, whereas 3g showed IC(50) of 41.9 mu M against Colo-205. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Aldehyde; beta-Naphthol; condensation; Cytotoxicity; One-pot reaction; Solvent-free; Tantalum(V) chloride; Xanthenes

Synthesis of the antibacterial benzoquinone primin and its water-soluble analogue, primin acid - Bhattacharya, Asish K.; Kaur, Tanpreet; Ganesh, Krishna N. (Synthesis-Stuttgart, 2010)
The biologically active natural product, primin and its water-soluble acid analogue, primin acid are prepared in 34% and 25% overall yields, respectively, from a common intermediate using a Grignard reaction and a Johnson-Claisen rearrangement as the key steps.
Keywords: 1; 4-benzoquinones; Antibacterial; Johnson-Claisen rearrangement; primin; primin acid

Synthesis of naturally occurring (+)-osmundalactone and 4-epi-(+)-osmundalactone from triacetyl-O-D-glucal - Kotammagari, Tharun K.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Tetrahedron Letters, 2015)
An efficient total synthesis of (+)-osmundalactone 1 has been achieved starting from readily available triacetyl-O-D-glucal 6 employing Ferrier rearrangement and Jones oxidation as key steps. Also, synthesis of 4-epi-(+)-osmundalactone 2 was accomplished from the common key intermediate 9. The absolute stereochemistry of (+)-osmundalactone 1 and a precursor of 4-epi-(+)-osmundalactone 2 have been established by single crystal X-ray analysis. The overall yield of compound 1 and 2 from triacetyl-O-D-glucal 6 is 13% and 8%, respectively. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Bioactive molecules; carbohydrates; D-glucal; Ferrier rearrangement; Pyrones

Synthesis of artemisinin derived glycoconjugates inspired by click chemistry - Goswami, Lakshmi; Paul, Sayantan; Kotammagari, Tharun K.; Bhattacharya, Asish K. (New Journal of Chemistry, 2019)
Herein we describe the synthesis of artemisinin based glycoconjugates (9a-i) through employing a Cu(i)-catalysed reaction between -propargylated dihydroartemisinin (7a) and azido sugars (8a-i), with moderate to excellent yields. Our synthesized artemisinin based glycoconjugates (9a-i) could prove to be an interesting class of bioactive molecules, suitable for the study of their various biological activities.

Short review of synthetic routes for the antiepileptic drug (R)-lacosamide - Aratikatla, Eswar K.; Bhattacharya, Asish K. (Organic Process Research & Development, 2020)
The disease epilepsy affects people of all ages and is due to a chronic neurological disorder in the brain. According to a report by the World Health Organization, epilepsy is one of the most common global neurological diseases. (R)-Lacosamide (Vimpat) was introduced by UCB Pharma in 2008 for the treatment of partial-onset seizures in patients suffering from epilepsy. This review summarizes all of the available synthetic strategies reported for (R)-lacosamide, which will help medicinal chemists in the further development of its synthesis.
Keywords: antiepileptic drug; epilepsy; lacosamide; serine derivative; synthesis

Synthesis of artemisinic acid derived glycoconjugates and their anticancer studies - Kotammagari, Tharun K.; Paul, Sayantan; Barik, Ganesh K.; Santra, Manas K.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2020)
Glycoconjugates, due to their diverse functions, are widely regarded as biologically important molecules. Artemisinic acid 1 occurs naturally in the plant Artemisia annua and is considered to be the biogenetic precursor of the antimalarial drug, artemisinin 2. We report herein the design and synthesis of diverse artemisinic acid derived glycoconjugates. We have synthesized 12-O-artemisinic acid-glycoconjugates (7a-k) and 12-N-artemisinic acid-glycoconjugates (8a-k) by utilizing Cu(i)-catalyzed azide-alkyne cycloaddition reactions (Click chemistry) with various synthesized sugar azides (6a-k) in good to excellent yields along with two fluorescently labeled compounds, 12-O-artemisinic acid-glycoconjugate 11 and 12-N-artemisinic acid-glycoconjugate 12, to investigate the mode of action of these compounds in biological systems. All the synthesized artemisinic acid glycoconjugates were assayed for their efficacy against the MCF7 cell line. Our anticancer studies indicated that all the synthesized compounds inhibited the growth of MCF7 cells in a dose dependent manner, barring compounds 4 and 7d. However, these compounds exhibit moderate cytotoxicity, as is evident from their IC50 values.

Short review on the synthetic routes for the antiepileptic drug (S)-levetiracetam - Paul, Sayantan; Bhattacharya, Asish K. (Organic Process Research and Development, 2024)
Epilepsy is a chronic disorder characterized by recurrent unpredictable seizures. Levetiracetam (Keppra) was introduced by UCB for the treatment of partial onset seizures in patients above 16 years of age diagnosed with epilepsy. This review reports synthetic strategies available for the synthesis of (S)-levetiracetam and will certainly aid the quest for the development of new routes for its synthesis.
Keywords: antiepileptic drug; butyrolactam; epilepsy; levetiracetam; synthesis

Strategies employing transition-metal free conditions for C-C bond formation in indoles - Ghodake, Balaji M.; Paul, Sayantan; Bhattacharya, Asish K. (ChemistrySelect, 2024)
Indole motifs are omnipresent in nature and can be found in many natural products as well as pharmaceuticals. It is for this reason synthetic transformations of indole have become a topic of interest for the organic and medicinal chemist community for decades. In this review, we have emphasized the functionalization of indoles via transition-metal-free approaches. This review touches on many aspects in different sub-sections, which gives a proposition of the tactics employed for the functionalization of indoles and an overview of the road ahead. In this review, essentially transition-metal-free conditions for C-C bond formation reactions in indoles has been explored. This review describes various approaches of functionalization at the C-2, C-3, C-4 and C-7 position of indoles which comprises arylation, alkenylation, acylation, formylation, alkylation, bisindolyl and cyclization strategies. Also, strategies incorporating N-alkylation/arylation has also been covered. image
Keywords: Alkylation; Arylation; formylation; Indole; transition-metal free